Genetic analysis of RET gene mutation in children with Hirschsprung’s disease of Kazakh etnicity (Bangladesh Journal of Medical Science, 2026)
Background Hirschprung’s disease (HD) is a highly heritable neurocristopathy. Many mutations in different genes are associated with this disease, but the RET proto-oncogene plays a major role. Methods We conducted a prospective study of the RET gene by sequencing in 21 children of Kazakh ethnicity treated in 2022-2023 to determine the frequency of mutations. Results The gender ratio was 2:1. There were more boys (66.6%) than girls (33.4%). The mean age of children with HD at the time of diagnosis was 46.8 days. Short-segment HD was diagnosed in 10 (47.7%), longsegment HD in 8 (38.1%) and total colonic HD in 3 (14.2%) cases. Combination of HD with Down syndrome in our study was noted in 1 (4.7%) child. 20 (95%) out of 21 children received surgical treatment. RET gene mutation was found in 4 children, 3 of whom were paternally predisposed siblings. In this family, the children’s father and another female child had type 1 diabetes mellitus. A mutation in exon 1 of the RET gene was identified in the familial form in all three girls and their father. All sisters had severe types of HD: long-segment HD (2) and total colonic agangliosis (1). In one case of the long-segment HD, a mutation in the RET gene was detected in exon 10; in addition to her, there are 3 healthy brothers in the family. Conclusions The overall frequency of RET mutations in our study was 19%, of which 3 patients had mutations detected in exon 1 and one case in exon 10. All severe forms of HD were represented by female gender. According to literature data, the lesion of exon 1 of RET gene is mainly characteristic for total form of HD, whereas in our study 2 girls from one family were diagnosed with long-segment HD.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 806-811